Outline of vocational training in zambia - Australian Dept. Of Labour And National Service, Perth; Australian Dept. of Labour and National Service, Perth ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
The 1963 population of zambia was approximately 3.5 million. The 8-year primary education program is followed by secondary, secondary technical, and trade school options. There is an increase in adult education at the primary and secondary levels. Craft and technician level programs are conducted at northern technical college and its ancillary centers. Evelyn hone college of further education is concerned with commercial and business training, communication, hotel and catering trades, home economics, adult education, applied science, telecommunications, and, in the future, engineering and construction. Trade courses are available in three trade schools, and other training establishments, under government departments, offer courses for upgrading civil service employees and training agricultural technicians, veterinary staff, nurses, medical technicians, and health inspectors. Technical teachers are trained in local centers and in overseas courses. Apprenticeship is organized in 46 trades under government supervision. In-industry training programs are promoted and developed by the government. It is proposed to set up building trades training centers under government sponsorship for accelerated training for building operatives. The adviser for further education has initiated a comprehensive scheme for training learner craftsmen, technicians, and technologists. Recommendations are being implemented to provide the necessary specialist administration and coordination of technical education and to obtain the necessary qualified personnel. (jm)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Apprenticeships; Economic Development; Educational Planning; Foreign Countries; General Education; Industrial Training; Teacher Education; Technical Education; Vocational Education; ZAMBIA